Aggregation Effect on Phthalocyanine Photocatalytic Degradation Efficiency Using Orange G and Methyl Orange as Test‐pollutant Compounds in Aqueous Medium. Issue 38 (13th October 2022) - Yılmaz, Yusuf; Özdemir, Mecit; Sanusi, Kayode; Fatomi, Nafisat O.; Khoza, Phindile B.
Abstract: The effect of aggregation on the photocatalytic behavior of two different water‐soluble phthalocyanines (Pcs) bearing four carboxylic‐acid‐functionalized thiophenyl groups, tetrathiophenycarboxyphthalocyanine (H2 TCPc) and tetrathiophenycarboxyphthalocyaninato Zn(II) complex (ZnTCPc) have been investigated. The two compounds, H2 TCPc and ZnTCPc, showed considerable solubility in water at pH ≈ 7.4, but were found to aggregate even at a concentration as low as 2.5×10 −5  M. Two organic dyes, orange G (OG) and methyl orange (MO), were employed as test‐pollutants which were photodegraded in the presence of the Pcs, with and without Triton X‐100 (TX) surfactant. H2 TCPc in the absence and presence of TX showed degradation efficiency (DE) of 5.80 and 8.70 % respectively, for OG degradation. For the same OG degradation, ZnTCPc as photocatalyst gave DE of 6.41 and 28.0 % in the absence and presence of TX, respectively. Whereas for the degradation of MO, H2 TCPc DE values were respectively found to be 11.0 and 39.0 % in the absence and presence of TX, while ZnTCPc gave 13.3 and 66.0 %, respectively. The ZnTCPc showed considerable low aggregation compared to H2 TCPc in the presence of TX, thus resulting in higher DE compared to that of the latter by a factor of 3.2 and 1.7 for OG and MO degradation, respectively. The singlet oxygen quantum yields (Φ▵ ) obtained for the two Pcs support the observed DE values, and were measured to be 0.50 (50 %) and 0.12 (12 %) for the ZnTCPc and H2 TCPc, respectively. The DFT/TDDFT calculated triplet yields for ZnTCPc (0.79) and H2 TCPc (0.020), showed linear correlation with their experimental Φ▵ yields. Abstract : Aggregation was shown to significantly reduce the photocatalytic degradation efficiencies of phthalocyanines (Pcs) in aqueous media. The two test‐pollutants, orange G and methyl orange employed, were moderately photodegraded in the presence of Pcs and Triton X‐100 (TX). The TX significantly enhanced photodegradation because it facilitated the Pc de‐aggregation into monomers.